Personal Branding Digital dalam Meningkatkan Keberhasilan Bisnis Gen Z di Era Society - Eliana Putri; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of the Society 5.0 era has driven significant changes in how young generations build their identities and develop digital-based enterprises. This study focuses on the role of digital personal branding in enhancing the business success of Generation Z, a group known for its high adaptability to technology and social media. Personal branding is understood not merely as a self-promotion strategy but also as a form of digital identity representation that influences public perception, consumer trust, and business competitiveness. This research employs a literature review method with a conceptual approach, examining various scholarly publications, official reports, and relevant articles from recent years. Data were collected through systematic searches across journal databases such as Google Scholar, Garuda Kemdikbud, SINTA, and DOAJ, and analyzed using content analysis techniques to identify patterns, trends, and relationships among variables related to digital personal branding and Gen Z business activities.The findings indicate that Generation Z strongly tends to utilize digital platforms as a medium for identity formation and business marketing. Dominant personal branding practices such as storytelling, visual consistency, niche specialization, and digital collaboration have been shown to strengthen professional image and expand audience reach. The results also reveal that digital personal branding significantly impacts business success by increasing credibility, customer loyalty, and collaboration opportunities. This success is strongly influenced by factors such as authenticity, content quality, audience interaction, and the ability to understand social media algorithms.In conclusion, digital personal branding serves as a strategic asset that has the potential to enhance the competitiveness and business growth of Generation Z within an increasingly competitive digital ecosystem.